Genomics of foodborne pathogens for microbial food safety. (February 2018) - Allard, Marc W; Bell, Rebecca; Ferreira, Christina M; Gonzalez-Escalona, Narjol; Hoffmann, Maria; Muruvanda, Tim; Ottesen, Andrea; Ramachandran, Padmini; Reed, Elizabeth; Sharma, Shashi; Stevens, Eric; Timme, Ruth; et al.
Graphical abstract: Highlights: Genetic data makes comparisons transparent, for broad sharing across the disciplines. US FDA in combination with the NCBI developed the first distributed WGS network. WGS combined with phylogenetics and metadata makes for faster source-tracking. Need for genotype to phenotype predictions for pathogenicity and virulence. Fully closed genomes facilitates comparative analysis and new epigenetic discoveries. Metagenomic methods characterizing pathogens in foods remain expensive. Abstract : Whole genome sequencing (WGS) has been broadly used to provide detailed characterization of foodborne pathogens. These genomes for diverse species including Salmonella, Escherichia coli, Listeria, Campylobacter and Vibrio have provided great insight into the genetic make-up of these pathogens. Numerous government agencies, industry and academia have developed new applications in food safety using WGS approaches such as outbreak detection and characterization, source tracking, determining the root cause of a contamination event, profiling of virulence and pathogenicity attributes, antimicrobial resistance monitoring, quality assurance for microbiology testing, as well as many others. The future looks bright for additional applications that come with the new technologies and tools in genomics and metagenomics.